Successes and challenges towards improving quality of primary health care services: a scoping review - Aklilu Endalamaw; Resham B Khatri; Daniel Erku; Frehiwot Nigatu; Anteneh Zewdie; Eskinder Wolka; Yibeltal Assefa (BMC, 2023)
Abstract Background Quality health services build communities' and patients' trust in health care. It enhances the acceptability of services and increases health service coverage. Quality primary health care is imperative for universal health coverage through expanding health institutions and increasing skilled health professionals to deliver services near to people. Evidence on the quality of health system inputs, interactions between health personnel and clients, and outcomes of health care interventions is necessary. This review summarised indicators, successes, and challenges of the quality of primary health care services. Methods We used the preferred reporting items for systematic reviews and meta-analysis extensions for scoping reviews to guide the article selection process. A systematic search of literature from PubMed, Web of Science, Excerpta Medica dataBASE (EMBASE), Scopus, and Google Scholar was conducted on August 23, 2022, but the preliminary search was begun on July 5, 2022. The Donabedian's quality of care framework, consisting of structure, process and outcomes, was used to operationalise and synthesise the findings on the quality of primary health care. Results Human resources for health, law and policy, infrastructure and facilities, and resources were the common structure indicators. Diagnosis (health assessment and/or laboratory tests) and management (health information, education, and treatment) procedures were the process indicators. Clinical outcomes (cure, mortality, treatment completion), behaviour change, and satisfaction were the common indicators of outcome. Lower cause-specific mortality and a lower rate of hospitalisation in high-income countries were successes, while high mortality due to tuberculosis and the geographical disparity in quality care were challenges in developing countries. There also exist challenges in developed countries (e.g., poor quality mental health care due to a high admission rate). Shortage of health workers was a challenge both in developed and developing countries. Conclusions Quality of care indicators varied according to the health care problems, which resulted in a disparity in the successes and challenges across countries around the world. Initiatives to improve the quality of primary health care services should ensure the availability of adequate health care providers, equipped health care facilities, appropriate financing mechanisms, enhance compliance with health policy and laws, as well as community and client participation. Additionally, each country should be proactive in monitoring and evaluation of performance indicators in each dimension (structure, process, and outcome) of quality of primary health care services.